Crustal and Upper Mantle Imaging of Botswana Using Magnetotelluric Method - Akinremi, Stephen; Fadel, Islam; van der Meijde, Mark (Frontiers in Earth Science, 2022)
We used magnetotelluric data from 352 sites in Botswana to derive a country-wide electrical conductivity model of the crust and upper mantle structure. A robust methodological scheme and 3D inversion were used to derive a 3D electrical conductivity model with unprecedented spatial coverage. The model results show interesting features, including the major cratonic blocks and the mobile belts in Botswana. A distinctive resistive structure was imaged in southwest Botswana, which suggests the existence of the Maltahohe microcraton as a separate cratonic unit as proposed by other studies. Furthermore, the model gives new insight into the extension of the East African Rift System to Botswana and the incipient rifting in the Okavango Rift Zone. In northern Botswana, the electrical conductivity model shows a highly conductive structure beneath the Okavango Rift Zone, which connects with a deeper conductive structure that we attribute to the East African Rift System due to its vicinity to Lake Kariba, the last surface expression of the rift system. We suggest that ascending fluids or melt from the East African Rift System causes the weakening of the lithosphere and plays a significant role in the incipient continental rifting in the Okavango Rift Zone.